Seizure Prediction and Detection via Phase and Amplitude Lock Values - Myers, Mark H.; Padmanabha, Akshay; Hossain, Gahangir; de Jongh Curry, Amy L.; Blaha, Charles D. (Frontiers in Human Neuroscience, 2016)
A robust seizure prediction methodology would enable a ‘closed-loop’ system that would only activate as impending seizure activity is detected. Such a system would eliminate ongoing stimulation to the brain, thereby eliminating such side effects as coughing, hoarseness, voice alteration, and paresthesias (Murphy et al., 1998, Ben-Menachem, 2001), while preserving overall battery life of the system. The seizure prediction and detection algorithm uses Phase/Amplitude Lock Values (PLV/ALV) which calculate the difference of phase and amplitude between EEG electrodes local and remote to the epileptic event. PLV is used as the seizure prediction marker and signifies the emergence of abnormal neuronal activations through local neuron populations. PLV/ALVs are used as seizure detection markers to demarcate the seizure event, or when the local seizure event has propagated throughout the brain turning into a grand-mal event. We verify the performance of this methodology against the ‘CHB-MIT Scalp EEG Database’ which features seizure attributes for testing. Through this testing, we can demonstrate a high degree of sensivity and precision of our methodology between pre-ictal and ictal events.